International relations : all that matters - Booth, Ken, 1943- (Great Britain : Hodder & Stoughton, 2014)
Booth explains that international relations are a critical level in the business of determining who gets what across the world. He gives an introduction and shows how they directly or indirectly affect all our lives.
Understanding the world -- Anarchy, system, states -- Theories, concepts, debates -- Fear, power, security -- Conflict, co-operation, statecrafe -- Political economy, capitalism, globalization -- Values, ethics, choices -- Inventing humanity -- 100 ideas.
Includes bibliographical references, filmography (pages 138-139), and index.
Keywords: International relations; International relations -- Philosophy